Asymmetric effect of oil price on economic growth: Panel analysis of low-income oil-importing countries - Motunrayo O. Akinsola; Nicholas M. Odhiambo (Energy Reports, 2020)
This paper examines the impact of oil price on economic growth in seven low-income oil-importing sub-Saharan African (SSA) countries, namely Ethiopia, Gambia, Mali, Mozambique, Senegal, Tanzania and Uganda. Using panel-Auto Regressive Distributive Lag (panel-ARDL), we examined the impact of oil price on economic growth in the short and long run. The results show that oil price does not have a significant impact on economic growth in the short run for the group, but has a negative significant impact in the long run. However, the short-run country coefficients show that oil price has a significant but mixed effect on economic growth in all the seven countries. Using the Non-linear Autoregressive Distributed Lag (NARDL) model, we also examined the asymmetric effect of oil price on economic growth by decomposing oil price into negative and positive changes. The advantage of this model is that it examines both the long-run and short-run asymmetric effects of real oil price on growth. We found that a decrease in oil price has a positive and significant impact on growth, while oil price increase has a significant negative effect. Moreover, the error correction terms are negative and statistically significant for both the PMG and five of the countries in the short-run country coefficients. Therefore, it would be important for policymakers to explore and implement efficient energy policies and employ technological advancement policies to mitigate oil price risks, especially in the long run.
Keywords: Q43; O55; N17; C33; 330; Economic growth; Asymmetric effect; Low-income countries; Oil price; Panel-ARDL